PENGARUH RETURN ON ASSETS DAN NET PROFIT MARGIN TERHADAP EARNING PER SHARE PADA PERUSAHAAN SUB SEKTOR AUTOMOBILE DAN KOMPONEN YANG TERDAFTAR DI IDX PERIODE 2018-2022 - Adli, Faisal; Agusentoso, Randhy (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of Return On Assets and Net Profit Margin partially and simultaneously on earnings per share in Automobile and Component Subsector Companies listed on the Indonesia Stock Exchange in 2018 - 2022. The type of research used is quantitative research with a descriptive approach. The population in this research is all financial reports of Automobile and Component Subsector Companies listed on the Indonesia Stock Exchange for 2018 - 2022. The research sample was determined using a purposive sampling technique, namely balance sheet and profit and loss. The data source in this research is secondary data taken from official website PT Selamat Sempurna Tbk., PT Prima Alloy Steel Universal Tbk., PT Gajah Tunggal Tbk., PT Multi Prima Sejahtera Tbk., dan PT Indo Spring Tbk. The data analysis technique in this research uses panel data regression analysis. The results of this research show that the Return On Assets has a significant value of 0.0259 < 0.05, has a partially significant effect on earnings per share, and the Net Profit Margin has a significant value of 0.2606 > 0.05, has a partially significant effect on earnings per share and Return On Assets. and the Net Profit Margin has a significant value of 0.003519 < 0.05, which simultaneously has a significant effect on earnings per share. The results of the analysis of the coefficient of determination with an Adjusted R-squared value of 0.347258, give the understanding that 34.72% of the dependent variable, namely EPS, can be explained by the independent variables, namely ROA and NPM. Meanwhile, the remaining 65.28% is influenced by other factors outside the variables used.